Relationship between Attention and Clarity in the Work Environment from a Cognitive and Organizational Perspective - Murillo , Hernán Javier Guzmán; Ortega, José Marcelo Torres; Niebles, William (Journal of Ecohumanism, 2024)
This study analyzes the relationship between Attention and Clarity in the organizational environment, analyzing how the perception of clarity in work processes can influence the ability of employees to maintain attention in their tasks. The research is based on theories on information processing, cognitive regulation and efficiency in performance, considering that clarity in organizational procedures and objectives facilitates concentration and reduces cognitive load. It is hypothesized that an increase in clarity in work processes is associated with an improvement in employee attention, suggesting that well-structured organizational environments can enhance individual performance. To evaluate this relationship, a quantitative design based on econometric techniques was used. The estimated simple linear regression model shows that the coefficient of the Clarity variable is positive and significant (p<0.001p < 0.001), indicating that employees who perceive greater clarity in their work environment tend to manifest a greater attention span in their activities. In addition, the model meets the fundamental assumptions of regression, including tests of specification, linearity, and absence of autocorrelation, allowing for reliable interpretation of the results. The findings suggest that organizational clarity is a factor that influences work care, which has implications in the design of organizational strategies aimed at performance optimization. It is recommended that future research extend the analysis by incorporating moderating variables such as task complexity and workload, in order to better understand the mechanisms underlying this relationship